Tail-Biting Trellises for Linear Codes and their Duals - Nori, Aditya; Shankar, Priti (Proceedings of the Forty-First Annual Allerton Conference on Communication, Control and Computing (Allerton), 2003)
The construction of dual tail-biting trellises from primal ones is an important problem in trellis based decoding algorithms for linear codes. Generalizations of two well known labeling algorithms, the Massey [3] and the BCJR [1] algorithms are presented for the construction of tail-biting trellises. The construction techniques lead directly to an algorithm for construction of a dual trellis from an algebraic description of the primal one, satisfying the property that the two trellises have identical state-complexity profiles.